Fibre direction strain measurement in a composite ply under pure bending using Digital Volume Correlation and Micro-focus Computed Tomography. (June 2020) - Schöberl, Erich; Mavrogordato, MN; Sinclair, I; Spearing, SM
This paper presents an experimental demonstration and validation of high-resolution three-dimensional experimental strain measurement using Digital Volume Correlation (DVC) on Carbon Fibre-Reinforced Polymers, via through-thickness strain analysis under a state of pure bending. To permit the application of DVC to displacements and/or strain measurements parallel to the fibre direction in well-aligned unidirectional materials at high volume fractions, a methodology was developed for the insertion of sparse populations of 400 nm BaTiO3 particles within the matrix to act as displacement trackers (i.e. fiducial markers). For this novel material system, measurement sensitivity and noise are considered, along with the spatial filtering intrinsic to established DVC data processing. In conjunction with Micro-focus Computed Tomography, the technique was applied to a simple standard specimen subjected to a four-point flexural test, which resulted in a linear strain distribution through the beam thickness. The high-resolution, fibre-level strain distributions (imaged at a voxel resolution of ∼0.64 µm) were compared against the classical beam theory (Euler–Bernoulli) in incrementally decreasing averaging schemes and different sub-set sizes. Different sampling and averaging strategies are reported, showing that DVC outputs can be obtained that are in very good agreement with the analytical solution. A practical lower limit for the spatial resolution of strain is discerned for the present materials and methods. This study demonstrates the effectiveness of DVC in measuring local strains parallel to the fibre direction, with corresponding potential for calibration and validation of micromechanical models predicting various fibre-dominated damage mechanisms.